Behavioral responses of animals to habitat fragmentation (Zoological Records and Reviews, 2023)
Habitat fragmentation -- the process by which continuous habitat is divided into smaller, isolated patches surrounded bya matrix of modified land -- affects animal populations not only through direct reduction of available habitat area butthrough behavioural changes that alter movement decisions, foraging strategies, social structure, mating patterns, andstress physiology in ways that may precede and predict population-level decline. This review synthesises evidence from196 primary studies (2005-2023) examining the behavioural responses of European vertebrates to habitat fragmentationacross terrestrial, freshwater, and coastal ecosystems, evaluating six major behavioural domains: movement anddispersal, foraging and diet, social organisation, reproductive behaviour, stress physiology, and anti-predator behaviour.Movement responses to fragmentation are the most extensively documented: GPS telemetry studies show that 68.4% ofEuropean forest mammals increase their mean daily movement distances in fragmented landscapes (mean increase42.4 +- 12.4% vs. continuous forest reference), while simultaneously reducing matrix crossing frequency -- indicatingmovement cost avoidance that compounds patch-level isolation. Chronic stress responses -- elevated faecalglucocorticoid metabolites at fragment edges and in small isolated patches -- are documented in 14 European mammaland bird species, with stress levels inversely correlated with patch size and positively correlated with edge density.Behavioural responses vary substantially by taxon, matrix permeability, and landscape context, generating a complexinterplay between individual behavioural adaptation and population-level vulnerability. Implications for wildlife corridordesign, connectivity conservation, and fragmented landscape management under EU Nature Restoration Law arediscussed.
Keywords: EU Nature Restoration Law; wildlife corridors; foraging; connectivity; edge effects; stress physiology; dispersal; movement ecology; animal behaviour; habitat fragmentation